Anti-Halitosis Tooth Paste: From Persian Manuscripts toward Clinic - Atefeh Arabzadeh; Amir Azadi; Saeed Daneshamooz; Somayeh Karami; Mostafa Rezaei; Abdolali Mohagheghzadeh* (Research Journal of Pharmacognosy, 2018)
Background and objectives: Halitosis as a common dentistry ailment which has a prevalence of around 50% of the adult population. There are many dental formulations in traditional Persian pharmacy called “Gharagher”, “Mazmazeh”, “Sonoun”, etc for treatment of halitosis. In the present study, we have tried to describe the step by step modernization of traditional herbal advices for treatment of halitosis. Methods: Traditional Persian manuscripts were reviewed and dome herbs were selected for formulation of toothpaste. Qualitative and quantitative controls were performed on raw materials and toothpaste was formulated using the selected herbs. Pharmaceutical control tests including squeeze, centrifuge, conductivity, particle size, spreading, temperature related stability, and microbial limit tests were performed on the toothpastes. Results: A total of 31 medicinal plants from 24 plant families and 12 anti-halitosis “Sonoun”s  possessing anti-halitosis related properties were found. Syzygium aromaticum, Pistacia atlantica var. mutica, and Punica granatum var. pleniflora were selected for the formulation. Results of quality contril assays were in the accepted range of pharmacopeias. GC-MS analysis showed 15 and 16 components in P. atlantica and S. aromaticum oils, respectively. GC-FID results showed 85.15% α-pinene in P. atlantica and 5.28% eugenol in S. aromaticum. ATR-IR spectrum was used for control of P. granatum flowers. The organoleptic properties, phase separation, particle size and microbial tests of formulations showed an accepted shelf life for performing clinical trials. The results proved a good texture property as well as desirable abrasive properties of the toothpaste. Post production quality control tests indicated the proper feature of final product after packaging. Conclusion: Such model would be a straight forward rout from traditional medical manuscripts toward clinic.